Awareness, anchor and adjustment factors in the use of institutional repositories by Nigerian lecturers (2021)
Institutional repositories have been established in universities globally because of their immense benefits to various stakeholders, especially lecturers. However, the literature has confirmed that institutional repositories are little used by lecturers. Previous studies have examined attitudes and disciplines, for example, but there seems to be no study on anchor and adjustment factors. This study therefore investigated awareness and anchor and adjustment factors as determinants of use of institutional repositories by lecturers in Nigeria. A descriptive survey and a purposive sampling technique were used to select universities that had had functional institutional repositories for at least four years at the time of data collection. A questionnaire was used to collect data from 857 lecturers. The study reveals that awareness and anchor and adjustment factors are determinants of use of institutional repositories by lecturers in Nigerian universities. The study recommends that more awareness programmes should be organized by libraries and that lecturers should constantly use computers to improve their computer self-efficacy and computer playfulness.